THE EFFECT OF QUIZIZZ LEARNING MEDIA ON STUDENT LEARNING MOTIVATION SMK BM PANCA BUDI MEDAN - Raehana, Raehana (Lembaga Jurnal & Seminar Universitas Pembangunan Panca Budi, 2023)
The problem in this research is the low learning motivation of students. This study aims to analyze the effect of Quizizz on students' motivation to learn accounting at SMK BM Panca Budi Medan. This research was conducted at SMK BM Panca Budi Medan, located at Jalan Gatot Subroto KM 4,5. This research is an experimental type of research using an experimental design of one group pre-test post-test design . The population of this research is all students of class XII AK, totaling 51 students. The research sample was 2 class XII accounting students, namely class XII AK 1 and class XII AK 2 as an experimental class with learning using quizizz as a learning medium. The instruments used to collect data are questionnaires. The sampling technique used is Nonprobability Sampling.. The analytical technique used is the Paired Sample T Test using windows SPSS ver 25 software for. The results of this study indicate that there is an influence of quizizz on the motivation to learn accounting students at SMK BM Panca Budi Medan.